CONSTITUTIONAL LEGAL REGULATION OF THE YOUTH POLICY IN SUBJECTS OF THE RUSSIAN FEDERATION: PROBLEMS AND PROSPECTS ON THE EXAMPLE F THE STAVROPOL TERRITORY - Eleonora Sergeevna Navasardova; Svetlana Stepanovna Shevchuk (Вестник Северо-Кавказского федерального университета, 2022)
The article considers the issues of constitutional legal regulation of youth policy in the Stavropol terri- tory. Identified the author of the problems in the field of state youth policy in the Stavropol region is character- istic for many regions of the Russian Federation. The author made proposals on improvement of legislation of the Stavropol territory on youth policy.